2013
DOI: 10.1002/ppul.22945
|View full text |Cite
|
Sign up to set email alerts
|

Sixty-five years since the New York heat wave: Advances in sweat testing for cystic fibrosis

Abstract: The sweat test remains important as a diagnostic test for cystic fibrosis (CF) and has contributed greatly to our understanding of CF as a disease of epithelial electrolyte transport. The standardization of the sweat test, by Gibson and Cooke [Gibson and Cooke (1959) Pediatrics 1959;23:5], followed observations of excessive dehydration amongst patients with CF and confirmed the utility as a diagnostic test. Quantitative pilocarpine iontophoresis remains the gold standard for sweat induction, but there are a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 64 publications
2
63
0
3
Order By: Relevance
“…Lack of chloride ion reabsorption by CFTR in the sweat gland leads to high levels being lost in the sweat, typically > 100 mmol/l in comparison with values of < 30 mmol/l in healthy individuals. 9 Diagnosis can also be established on CFTR mutation testing, although, because of the large number of mutations, a negative test cannot rule out the diagnosis unless the entire CFTR gene has been sequenced; this is rarely employed as a first-line diagnostic tool and is reserved for difficult diagnoses. However, whereas previously it may have been sufficient to secure a diagnosis on the basis of a sweat test, with the recent development of mutation-specific small-molecule treatments, 10 it is becoming increasingly necessary for a patient's mutation(s) to be defined.…”
Section: Clinical Presentation Diagnosis and Disease Manifestationmentioning
confidence: 99%
“…Lack of chloride ion reabsorption by CFTR in the sweat gland leads to high levels being lost in the sweat, typically > 100 mmol/l in comparison with values of < 30 mmol/l in healthy individuals. 9 Diagnosis can also be established on CFTR mutation testing, although, because of the large number of mutations, a negative test cannot rule out the diagnosis unless the entire CFTR gene has been sequenced; this is rarely employed as a first-line diagnostic tool and is reserved for difficult diagnoses. However, whereas previously it may have been sufficient to secure a diagnosis on the basis of a sweat test, with the recent development of mutation-specific small-molecule treatments, 10 it is becoming increasingly necessary for a patient's mutation(s) to be defined.…”
Section: Clinical Presentation Diagnosis and Disease Manifestationmentioning
confidence: 99%
“…CFTR malfunction also causes obstruction of pancreatic and biliary ducts (resulting in nutrient malabsorption and liver disease), infertility (particularly in men), meconium ileus at birth, and diabetes [15][16][17][18]. Another characteristic feature of most CF patients is the elevated concentration of sodium chloride in sweat [19]. Restoration of anion transport in defective cells is therefore considered as an important goal of therapeutic strategies in CF.…”
Section: Introductionmentioning
confidence: 99%
“…This variation is likely not unique to individuals with CF, because studies of all patients presenting for sweat chloride testing found within-subject variability ranging between 8.3 and 20.2% (median coefficient of variation) (22,39). Site-to-site differences in measurement cause further variation among individuals with identical CFTR genotypes, particularly if different techniques are used for measurement (40,41). Although testing variability seems to be decreasing with time, revisiting methods to standardize sweat testing among centers could address this tractable source of variation.…”
Section: The Role Of Testing Variabilitymentioning
confidence: 99%